Literasi Keuangan dan Kinerja Sebagai Kunci Keberlangsungan UKM Wisata Kuliner Halal Kanigaran di Probolinggo - Hudzafidah, Khusnik; Rahmansyah, Ahmad Iskandar; Junaidi, Junaidi (ISAFIR: Islamic Accounting and Finance Review, 2024)
This study aims to analyze the impact of financial literacy on the sustainability of SMEs, with performance as an intervening variable, focusing on halal culinary SMEs in Kanigaran, Probolinggo. A quantitative approach was used in this study, with data analysis conducted using SmartPLS. The findings indicate that financial literacy significantly influences both the performance of SMEs and their sustainability, both directly and through the mediation of performance. Financial literacy aids business owners in better managing their finances, while SME performance strengthens business resilience in facing market challenges. This study contributes practically to policymakers by highlighting the need for financial literacy training programs and performance enhancement strategies to support the sustainability of SMEs. Additionally, the research provides academic implications on the importance of intervening variables in the relationship between financial literacy and SME sustainability.